Analisis Green Image, Perceived Csr Capability Dan Customer Perception Of CSR Activities: Ethical CSR Terhadap Customer Loyalty - Riska Ernawati; Ida Bagus Nyoman Udayana; LTH Hutami (Master: Jurnal Manajemen dan Bisnis Terapan, 2021)
This study aims to see the effect of Green Image on Customer Perceptions of CSR Activities: Ethical CSR, The Effect of CSR Capability on Customer Perceptions of CSR Activities: Ethical CSR and the influence of Customer Perceptions on CSR Activities: Ethical CSR on Customer Loyalty. The population in this study were students and students of Sarjanawiyata Tamansiswa University who had used or are still using products from The Body Shop, with a sample of 105 respondents. The sampling technique in this study used a non-probability sampling technique with purposive sampling.The results showed that there was a positive effect of green image on customer perception of CSR activities: ethical CSR, there was a positive influence on perceived CSR capability on customer perception of CSR activities: ethical CSR and there was a positive effect on Customer Perception Of CSR Activities: Ethical CSR on Customer Loyalty.